Pengaruh Pengetahuan Orang Tua Tentang Wajib Belajar, Ketersediaan Sarana Belajar di Rumah dan Kemampuan Mengajar Guru Terhadap Hasil Belajar IPS Terpadu - komang adnyana; I Komang Winahta; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This study aimed to whether there is an influence parental knowledge about compulsory education, availability of home study and teaching capabilities of teachers to the learning outcomes of IPS Integrated eighth grade students. The population is 158 students with a sample of 113 students, which is taken by random sampling technique. The technique used to collect the data were observation, documentation, interviews, and questionnaires. To test this hypothesis one, two, and three using a simple linear regression model and the fourth hypothesis using multiple regression models. Based on data analysis results show that: (1)There is the influence of parental knowledge about compulsory education learning outcomes IPS Integrated eighth grade students of SMP Negeri 1 Sekampung. (2)There is the influence of availability of home study learning outcomes IPS Integrated eighth grade students of SMP Negeri 1 Sekampung. (3)There is the influence of teachers' ability to teach social studies learning outcomes Integrated eighth grade students of SMP Negeri 1 Sekampung. (4)There is the influence of parental knowledge about compulsory education, ketersediaaan means of learning at home and teaching capabilities of teachers to the learning outcomes of IPS Integrated eighth grade students of SMP Negeri 1 Sekampung.